A perspective on alloy effects between polymer additives in the development of nondust blends: A DSC and spectroscopic evaluation. Issue 2 (9th August 2021) - Allen, Norman S.; Edge, Michele; Hussain, Sajid
Abstract: The optimum synergistic melt blending of 18 antioxidants and light stabilizers has been evaluated using differential scanning calorimetry (DSC) analysis and melting point phase plots obtained to evaluate any effective true eutectic mixtures. Although only three systems gave true eutectic mixtures, optimum lower temperature melt blends were possible up to 230°C. Systems with Lowilite 26 and Cyasorb 1164 showed effective eutectic mixtures especially with hindered piperidine stabilizers while those based on Anox 20 and Lowilite 62 were poor. Eutectic mixtures between aromatic phenolics and amines infer that they are not simply a mechanical mixture of the two components, but a preferential ordering of atomic planes occurs during their formation associated with intermolecular hydrogen bonding. Fourier transform infra‐red spectroscopy (FTIR) and ultra‐violet (UV) absorption analysis showed in some cases strong bonding interactions between some of the additives where hydroxyl, amine, and carbonyl groups can potentially interact. This was especially notable where strong eutectic behavior was observed for benzophenone absorbers, where alkoxy substitution (Lowilite 22) was replaced by hydroxyl groups (Lowilite 24). Strong interaction between hindered piperidine and phenolic antioxidants also gave effective eutectic lattice phases. The analysis is discussed in relation to potential outcomes for the use of additive melt blends in polymer stabilization. Abstract : Formation of Eutectic Melt blend between light stabilisers.